DIAGNOSTIC BARRIERS IN CHILDREN WITH IMMUNODEFICIENCIES IN CENTRAL ASIA: A CASE-BASED DISCUSSION - Dauyey, Zhanna; Poddighe, Dimitri (MDPI, 2021)
Common variable immunodeficiency (CVID) is a primary immune deficit (PID) mainly characterized by hypogammaglobulinemia. In addition to increased susceptibility to infections and several immune-mediated manifestations, patients with CVID frequently develop bronchiectasis because of recurrent respiratory infections. This occurrence could be more likely if the diagnosis of CVID is delayed, as it often happens in less resourced clinical settings. A 15-year-old female patient was admitted to a tertiary hospital in Kazakhstan for consultation regarding a previous and established diagnosis of bronchiectasis. The clinical history was characterized by recurrent respiratory infections for several years, in addition to the development of a mixed restrictive-obstructive respiratory syndrome. Therefore, she underwent chest computerized tomography, which confirmed the presence of multiple and bilateral bronchiectasis. The clinical discussion on this patient highlighted that serum immunoglobulins were never measured previously and, thus, their assessment was strongly recommended. Based on that, a diagnosis of CVID was finally achieved, and the patient started the appropriate immunoglobulin replacement therapy. To our knowledge, this report is the first English-language publication on CVID and bronchiectasis from Central Asia. Bronchiectasis is currently an important medical problem in developing countries and populations with low socioeconomic status, where the diagnosis of the underlying cystic fibrosis and non-cystic fibrosis comorbidities can be delayed and more difficult than in countries with more accessible health care systems and facilities. This case report emphasized this important clinical issue in Central Asia and should raise the medical attention and awareness of this health problem, in order to improve the diagnostic timing and rate.
Keywords: bronchiectasis; pediatric hypogammaglobulinemia; common variable immunodeficiency; Kazakhstan; Central Asia; diagnostic delay; Type of access: Open Access